2003
DOI: 10.1063/1.1555679
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Yb–Er energy transfer in fluorozirconate glass

Abstract: The mechanism of the Yb 3ϩ →Er 3ϩ energy transfer as a function of the donor and the acceptor concentration was investigated in Yb 3ϩ -Er 3ϩ codoped fluorozirconate glass. The luminescence decay curves were measured and analyzed by monitoring the Er 3ϩ ( 4 I 11/2 ) fluorescence induced by the Yb 3ϩ ( 2 F 5/2 ) excitation. The energy transfer microparameters were determined and used to estimate the Yb-Er transfer rate of an energy transfer process assisted by excitation migration among donors state ͑diffusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 19 publications
1
26
2
Order By: Relevance
“…In this case, ET1 efficiency exhibits a similar Tm concentration dependence as was observed for the case of Tm→Ho ET, however with a slight increase of the fast excitation diffusion critical radius (R C ϭ14.5 Å). Based on our previous report, 8 it was demonstrated again, in the present work, that the method of analyzing the time dependence of the luminescence from the acceptor viewpoint is an important tool to investigate the mechanism of the energy transfer among rare-earth ions in solids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, ET1 efficiency exhibits a similar Tm concentration dependence as was observed for the case of Tm→Ho ET, however with a slight increase of the fast excitation diffusion critical radius (R C ϭ14.5 Å). Based on our previous report, 8 it was demonstrated again, in the present work, that the method of analyzing the time dependence of the luminescence from the acceptor viewpoint is an important tool to investigate the mechanism of the energy transfer among rare-earth ions in solids.…”
Section: Discussionmentioning
confidence: 99%
“…11 Based on this observation, we concluded that the Tm-Ho ET and Tm-Tm CR are a fast-excitation diffusiondependent energy transfer mechanism similar to the one observed for the Yb→Er energy transfer in ZBLAN glass. 8 As a consequence, the hypothesis on the occurrence of fast excitation diffusion occurrence before the direct D* -A resonant energy transfer is reinforced.…”
Section: ͑14͒mentioning
confidence: 97%
See 1 more Smart Citation
“…For example, previous research has investigated fabricating erbium and ytterbium doped microtoroid resonant cavity-based lasers using either ion implantation or sol-gel techniques [26][27][28]. While these detailed studies did successfully demonstrate single ion doped toroid microlasers, it is well-known that co-doped lasers have significantly improved performance over single doped devices, because the absorption efficiency of the primary dopant is increased by the secondary dopant (sensitizer) [29,30]. The Er…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has investigated fabricating single ion doped toroid microlasers, ie erbium and ytterbium doped microtoroid resonant cavity lasers using either sol-gel techniques or ion implantation [25][26][27]. However, it is well-known that co-doped lasers have significantly improved performance over single doped devices, because the secondary dopant (sensitizer) can increase the absorption efficiency of the primary dopant [28,29]. In this work, an ultra-low threshold co-doped microlaser is made by combining the large optical cross section of Er 3+ :Yb 3+ co-doped sol-gel and with the high circulating intensities present in ultra-high-Q optical microcavities.…”
Section: Introductionmentioning
confidence: 99%